ijps 2019
DOI: 10.36468/pharmaceutical-sciences.594
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antimicrobial, Antioxidant and Cytotoxic Activities of Dialium cochinchinensis Seed Extract

Abstract: Bui et al.: Antimicrobial, antioxidant and cytotoxic activities of Dialium cochinchinensisThis study was undertaken to evaluate the phytoconstituents present in the seed extract of Dialium cochinchinensis for antioxidant, antimicrobial and cytotoxic properties. Results showed the presence of polyphenols, flavonoids, alkaloids, saponins, coumarins and a polyuronid compound in the Dialium cochinchinensis seed extract. The total polyphenol and flavonoid contents of the dry extract were 133.5±2.87 mg GAE/g and 227… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…According to present study, the concentration of extract and percentage inhibition showed a linear relationship which means that the higher the concentration of plant extract the more is the scavenging property which is similar to the Bui et al [58] .…”
Section: Resultssupporting
confidence: 82%
“…According to present study, the concentration of extract and percentage inhibition showed a linear relationship which means that the higher the concentration of plant extract the more is the scavenging property which is similar to the Bui et al [58] .…”
Section: Resultssupporting
confidence: 82%
“…This SI value was important because it indicates the safe value of plant extract for antiviral activity. A high value of SI indicated a large safety margin between beneficial and toxic doses [22]. As in the previous study, the antiviral activity with an SI value of more than 10 can be considered to possess a high potential for an antiviral agent [14].…”
Section: Antiviral Screeningmentioning
confidence: 52%
“…In comparison with some species of the genus Dialium, this activity appears to be much greater. Indeed, the antioxidant activity on DPPH, expressed as IC50 in μg / mL, of several species of the genus Dialium is reported in the literature, D. indum, 181.6 ± 0.4 [33,34], D. guineense, 50.23 ± 0.15 [35], D. corbisieri, 14.44 ± 0.12 and D. gossweileri, > 500 [36], D. cochinchinensis, 65.01 ± 0.12 [37]. This interesting antioxidant activity observed in D. angolense would be linked to the presence of phenolic compounds mainly flavonoids, identified and quantified within the plant during this study (table 2), as well as several previous studies which testify to the antioxidant activity of flavonoids [38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%